The Debate About the Almighty שַׁדַּי (Saddai) in the Book of Job - Ragil Kristiawan; Joko Priyono; Kim Kiedong (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2025)
This study aims to fill the interpretive gap in the Book of Job by analysing the use of yD:êv (Saddai) in the dialogues and debates in the Book of Job, and how this name becomes a bridge between the concept of divine justice and the human experience of suffering. The research method is qualitative with a hermeneutic approach, where the author compares the Masoretic and Septuagint (LXX) texts, where the author analyses the dynamics of the use of yD:êv (Saddai) by various characters in the book of Job. The results show that the name yD:êv Saddai reflects God's infinite power and permits suffering as a form of discipline. The discussion highlights the dynamics of dialogue between Job and his friends, as well as the theological implications of suffering as a space to experience God's love. The conclusion of this study asserts that an understanding of Saddai can provide new insights into biblical theology and human spiritual experience.